2014
DOI: 10.1016/j.ijggc.2014.06.024
|View full text |Cite
|
Sign up to set email alerts
|

The effects of SO2 contamination, brine salinity, pressure, and temperature on dynamic contact angles and interfacial tension of supercritical CO2/brine/quartz systems

Abstract: The successful implementation of geologic CO 2 sequestration schemes in deep saline aquifers requires storage sites with minimum risk of CO 2 leakage through the caprock and maximum storage capacity in the reservoir rock. Some of the essential parameters that affect the effectiveness of a storage scheme are the density of CO 2 , the interfacial tension between CO 2rich and aqueous phases, and the wettability of reservoir rock and caprock in contact with these fluids at reservoir conditions [1]. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 32 publications
9
107
0
Order By: Relevance
“…(1) Data that we transcribed from published tables (Experiments 10-12 in Table 1 of Broseta et al, 2012; Table 2 of Saraji et al, 2013 and Table 1 of Saraji et al, 2014).…”
Section: Datamentioning
confidence: 99%
See 4 more Smart Citations
“…(1) Data that we transcribed from published tables (Experiments 10-12 in Table 1 of Broseta et al, 2012; Table 2 of Saraji et al, 2013 and Table 1 of Saraji et al, 2014).…”
Section: Datamentioning
confidence: 99%
“…Despite being a potential source of "spurious effects on measurements" (Farokhpoor et al, 2013a) that warrants "a thorough surface preparation" , surface roughness is often unreported in published accounts of contact angle measurements. Only five of the studies examined in our analysis (Jung and Wan, 2012;Saraji et al, 2013Saraji et al, , 2014Wang et al, 2013;Sarmadivaleh et al, 2015) reported the roughness of the surfaces tested and surface roughness was therefore not included in our models. We note, however, that the inclusion of the study as a random effect will accommodate some of the between-study variability associated with unmeasured laboratory parameters such as surface roughness.…”
Section: Statistical Heterogeneitymentioning
confidence: 99%
See 3 more Smart Citations